IMPLEMENTING PROCESS WRITING APPROACH TO IMPROVE THE WRITING SKILL OF THE SECOND SEMESTER STUDENTS OF NUSANTARA PGRI KEDIRI UNIVERSITY - Riwayatiningsih, Rika - (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2015)
The design of this study is a classroom action research. The objective of this study is to investigate how the process writing approach improves the writing skill on the second semester students of  English Department at Nusantara PGRI kediri University. Based on the findings and discussions of this study, it can be concluded that the process writing approach could improve the students’ ability in writing a recount text. It was shown by all the subjects who reached significant improvements on each stage of writing. Firstly, most of the subjects or 75% of them were able to explore, select, and order ideas to make a good outline. Secondly, 75% of the students were able to jot down their ideas on the paper which focused on the content and meaning as a development of their outline. Thirdly, 79% of them were able to revise their draft for content clarity of meaning as the teacher suggested. They were able to check the draft whether it had already contained an orientation, event and reorientation or not and also checked whether each paragraph contained a topic sentence, add or delete all supporting details for unity, and rearrange ideas for coherence. Fourthly, 83% of them were able to do peer-editing activity.